1991
DOI: 10.1017/s0144686x00003986
|View full text |Cite
|
Sign up to set email alerts
|

Communication, Language and the Institutionalised Elderly

Abstract: Research describing the social world of elderly residents of nursing homes is organised in this paper into three levels of analysis: the institutional level, the relational level and the interactional level. The significance of each level is highlighted, with special attention being given to the interactional level of analysis and the study of language within the nursing home. Data gathered from semi-structured interviews with both elderly residents and nurse aides are presented and interpreted as evidence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
18
0

Year Published

1993
1993
2005
2005

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 26 publications
3
18
0
Order By: Relevance
“…As predicted, a positive correlation between the RCS and the Relationship VAS existed; that is, residents who rated their care providers as reliable and empathic also rated their relationships as close. The positive association between close relationships and care providers who relate well is consistent with Nussbaum's (1991) and Gilleard and Reed's (1998) findings. Nussbaum proposed that the talk within the nurse-resident interaction reveals the nature and the closeness of the relationship and suggested that researchers focus not only on the institutional level (i.e., skill mix, care models, number of personnel) when evaluating quality of care, but also on the relational level.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…As predicted, a positive correlation between the RCS and the Relationship VAS existed; that is, residents who rated their care providers as reliable and empathic also rated their relationships as close. The positive association between close relationships and care providers who relate well is consistent with Nussbaum's (1991) and Gilleard and Reed's (1998) findings. Nussbaum proposed that the talk within the nurse-resident interaction reveals the nature and the closeness of the relationship and suggested that researchers focus not only on the institutional level (i.e., skill mix, care models, number of personnel) when evaluating quality of care, but also on the relational level.…”
Section: Discussionsupporting
confidence: 83%
“…Because the RBS was developed for elders with cognitive impairment and the RCS for those without cognitive impairment, further testing is required. Moreover, even though the RBS developed for persons with dementia operationalizes observable reliable and empathic behaviors of the care provider (i.e., staying with the resident, altering the pace of care, and focusing care beyond the task) these care provider behaviors have been found essential for residents without dementia as well (Kane, 2003;Nussbaum, 1991). The significant difference between residents' perceptions of relational care during a day and an evening shift is worth highlighting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a number of other status characteristics are also operating in this situation, notably age, race, mental capacity and ocial role, any or all of which might be more powerful than gender in determining interactions (Nussbaum, 1991). This study examines the relationship between gender and rate of interactions in a single long-term care unit.…”
mentioning
confidence: 98%
“…Sigman, 1986;Nussbaum, 1991). Bureaucratic rules determine when eating, bathing and hair dressing may take place, who may smoke, and how many cigarettes and the brands of cigarettes that are allowed.…”
Section: The Nursing Homementioning
confidence: 99%